A new host for Philornis torquans (Diptera, Muscidae) from the Brazilian Cerrado - Couri, Márcia Souto; Barbosa, Leandro; Marini, Miguel Ângelo; Duca, Charles; Pujol-Luz, José Roberto (Papéis Avulsos de Zoologia, 2018)
Philornis larvae and pupae were collected in nestlings of Neothraupis fasciata (Lichtenstein), the White-banded Tanager (Passeriformes, Thraupidae), in three breeding seasons, between October and November 2003‑2005 in a reserve in central Brazil. Here, we present biological data, diagnosis to the recognition of the species and a key to the segregation of species occurring in the Cerrado. The larvae were intradermic in the nestlings and the pupae were collected in the nests after the birds have abandoned them. The immatures collected were taken to the laboratory and reared under laboratory conditions, until emergence. The species identified as Philornis torquans (Nielsen), is here firstly recorded from the Brazilian Cerrado, and firstly recorded its association with N. fasciata. With this record, the number of Philornis species occurring in the Cerrado rises to three.